PENGARUH METODE BERCERITA MENGGUNAKAN MEDIA BUKU BERGAMBAR 3D TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN - Fadhilah Latief; Wa Wiwin Ali; Munirah Munirah (Jurnal Panrita, 2022)
This study aims to determine the effect of the storytelling method using 3D picture book media on the listening ability of children in the B3 group aged 5-6 years at TK Aisyiyah Bustanul Athfal 1 Tello Baru, Makassar city. This type of research is an experimental research method with pre-experimental designs that use the One Group Pretest-posttest design consisting of pretest, treatment and posttest, with the subjects in this study being group B3 children, totaling 10 children. The results of the study are based on the results of calculations using the Wilcoxon Signed Rank Test. In the SPSS program, the Asymp sig (2-tailed) value is 0.003, here the probability is below 0.05 or p <0.05, which means H0 is rejected. In accordance with if the probability (Asymp.sig) < 0.05 then H0 is rejected and H1, and if the probability (Asymp.sig) > 0.05 then H1 is accepted and H0 is rejected. So there is an effect of the storytelling method using 3D picture book media on the listening ability of group B children aged 5-6 years at Aisyiyah Bustanul Athfal 1 Tello Baru Kindergarten, Makassar city.